2012
DOI: 10.1182/blood-2012-04-423939
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced thrombocytopenia: MIBS trumps LIBS

Abstract: Understanding the pathogenesis of drug-induced immune thrombocytopenia is the key to better patient management. In this issue of Blood, Bougie and colleagues provide further useful insights into the mechanism of thrombocytopenia caused by arginine-glycine-aspartic acid (RGD) mimetic drugs.1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Pretreatment of FcγRIIa mAb (i.e., CD32), an ITAM-bearing transmembrane receptor responsible for α IIb β 3 outside-in signaling [16], completely inhibited platelet aggregation caused by TFV-3/AP2 ( Figure 4C), suggesting that FcγRIIa is essential for activation. 7 of 20 and elicited FcRIIa-mediated platelet aggregation [29] and platelet consumption [11]. The recent report also indicated that eptifibatide-induced thrombocytopenia is associated with an increase in circulating procoagulant platelet-derived microparticles [14].…”
Section: Combination Of Tfv-1 With Ap2 Does Not Induce Fcγriia-mediatmentioning
confidence: 98%
See 4 more Smart Citations
“…Pretreatment of FcγRIIa mAb (i.e., CD32), an ITAM-bearing transmembrane receptor responsible for α IIb β 3 outside-in signaling [16], completely inhibited platelet aggregation caused by TFV-3/AP2 ( Figure 4C), suggesting that FcγRIIa is essential for activation. 7 of 20 and elicited FcRIIa-mediated platelet aggregation [29] and platelet consumption [11]. The recent report also indicated that eptifibatide-induced thrombocytopenia is associated with an increase in circulating procoagulant platelet-derived microparticles [14].…”
Section: Combination Of Tfv-1 With Ap2 Does Not Induce Fcγriia-mediatmentioning
confidence: 98%
“…Immune thrombocytopenia occurs on first exposure to RGD-mimetic agents. That is, platelet count usually declines sharply within hours of the commencement of drug administration, demonstrating the presence of a naturally occurring antiplatelet antibody in patients who took these kinds of drugs [11]. Previous reports have revealed that upon binding of RGD-mimetic drugs to integrin IIb3, the ligand-binding capacity increased in the activated integrin and intrinsic antibodies recognized conformational changes in IIb3 induced by drugs [12].…”
Section: Tfv-1 Binding To Integrin Iib3 Does Not Prime the Resting mentioning
confidence: 99%
See 3 more Smart Citations